Climate change impact on selected European crops - Ivajnšič, Danijel; Zver, Aleš; Žiberna, Igor (Journal for Geography, 2019)
Climate change also affects food production. However, what will be the response of agricultural crops to future climate conditions across Europe is one of the key issues for the development, implementation and proper implementation of the new European agricultural policy. This paper addresses the potential response of selected European agricultural crops (wheat [Triticum aestivum L.], maize [Zea Mays L.], potato [Solanum tuberosum L.] and olive [Olea europaea L.]) to climate scenarios (RCP2.6, RCP4.5 and RCP8.5) in the second half of the 21st century (2070) by considering different global climate models (CC, HE and MP). Bioclimatic data from the ECOCROP database (temperature and precipitation ranges) for each considered crop and the WorldClim climatic database for Europe were used to develop maps showing the future potential crop climate suitability. The results confirm existing assumptions that, in general, the optimal climatic conditions for the production of selected crops will shift towards higher latitudes or altitudes. Indeed, this potential spatial shift is, of course, species specific and depends on many other natural and socio-economic factors.